Contribution of maize crop residues and fertilization to nitrogen nutrition of soybean grown under no-tillage system - Bruno, Isabeli Pereira; Franzini, Vinicius Ide; Muraoka, Takashi (Frontiers in Agronomy, 2025)
Nitrogen (N) is essential for plant growth and, consequently, a key factor in the productivity and sustainability of agriculture. Soybean and maize require large amounts of N during the growing season. Although soybean primarily relies on biological nitrogen fixation, this source alone does not meet the crop’s total N requirements. Maize-soybean rotation is common under no-tillage systems, but the contribution of maize stover and N fertilizer to the subsequent soybean crop had been unclear. This study used a two-season field experiment to quantify N uptake and recovery in maize and the following soybean crop. Maize was fertilized with increasing rates of N-urea, and 15N tracing was used to assess N dynamics in the shoots of both maize and the subsequent soybean. Most of the N in maize shoot was derived from the soil, with up to 37% originating from fertilizer. In both crops, grains were the primary N sink, and high yields were achieved. In soybean, N uptake from maize stover and residual fertilizer was minimal, with a maximum recovery of 9% in the grain. These findings reveal for the first time the limited short-term contribution of N-urea applied to maize and its stover to soybean nutrition, suggesting that soil N plays an important role in supplying N to the soybean system.